Caspase-mediated cleavage of eukaryotic translation initiation factor subunit 2alpha. - Satoh, S (1999)
Eukaryotic translation initiation factor 2alpha (eIF-2alpha), a target molecule of the interferon-inducible double-stranded-RNA-dependent protein kinase (PKR), was cleaved in apoptotic Saos-2 cells on treatment with poly(I).poly(C) or tumour necrosis factor alpha. This cleavage occurred with a time course similar to that of poly(ADP-ribose) polymerase, a well-known caspase substrate. In addition, eIF-2alpha was cleaved by recombinant active caspase-3 in vitro. By site-directed mutagenesis, the cleavage site was mapped to an Ala-Glu-Val-Asp(300) downward arrowGly(301) sequence located in the C-terminal portion of eIF-2alpha. PKR phosphorylates eIF-2alpha on Ser(51), resulting in the suppression of protein synthesis. PKR-mediated translational suppression was repressed when the C-terminally cleaved product of eIF-2alpha was overexpressed in Saos-2 cells, even though PKR can phosphorylate this cleaved product. These results suggest that caspase-3 or related protease(s) can modulate the efficiency of protein synthesis by cleaving the alpha subunit of eIF-2, a key component in the initiation of translation.